PERFORMA RETORIKA MARTY M. NATALEGAWA DALAM SESI PEMBUKAAN UNAOC 6 BALI - Bedjo Soekarno, Atsarina Luthfiyyah, Buddy Riyanto & (Transformasi, 2016)
This study was motivated by Marty M. Natalegawa as the representative of Indonesia forrhetoric, which successfully gave the effect of a follow-up on the implementation of UNAOC 6.This study described forms of rhetorical performance, mastery of the message, vocal strength,and visual aspects of Marty M. Natalegawa in UNAOC 6, Bali. The research had conducted indescriptive studies, document analysis, which focusing on observation and the circumstances.The researchers acted as an observer, which only made the category of behavior, observedsymptoms, and recorded observations.Keywords: UNAOC6, Performance of Rhetoric, Rhetoric of Marty M. Natalegawa